Actors and agency in academic language policy and planning. Issue 1 (2nd January 2016) - Fenton-Smith, Ben; Gurney, Laura
Abstract : Nearly two decades have passed since Kaplan and Baldauf [1997. Language planning from practice to theory . Clevedon: Multilingual Matters] drew attention to the dearth of language policy and planning (LPP) in higher education. Despite the continuing inflow of English as an additional language students into Anglophone universities, and a boom in English-medium instruction policies in non-Anglophone tertiary institutions [Dearden, J. (2014). English as a medium of instruction: A growing global phenomenon . British Council], LPP research remains relatively underdeveloped in higher education. We suggest that current understandings of academic language policy and planning in higher education would benefit from contextualised analyses of actors and agency [Chua, C. S. K., & Baldauf, R. B. (2011). Micro language planning. In E. Hinkel (Ed.), Handbook of research in second language teaching and learning (pp. 936–951). New York, NY: Routledge; Zhao, S. H., 2011. Actors in language planning. In E. Hinkel (Ed.), Handbook of research in second language teaching and learning (Vol. II, pp. 905–923). New York, NY: Routledge; Zhao, S. H., & Baldauf, R. B. (2012). Individual agency in language planning: Chinese script reform as a case study. Language Problems & Language Planning, 36 (1), 1–24]. In order to address this gap, we conducted semi-structured interviews with 10 academic language program planners at different universities across Australia. We examined how the micro-level processes of program development and implementation were both constrained and enabled by the participation of different actor groups, operating at different levels (micro, meso, macro) and each with their own capacity to influence change. We conclude by arguing that coherent university-wide language policies, formulated by decision-making bodies representative of a variety of stakeholder groups and sensitive to program implementation needs at the micro level, represent a step towards improving the current situation.